Experiences of Living in the Community for Older Aboriginal Persons With Dementia Symptoms in Taiwan. (15th May 2019) - Chen, Mei-Chen; Huang, Hsiu-Li; Chiu, Yi-Chen; Yip, Ping-Keung; Wu, Suh-Mian; Hsu, Wen-Chuin; Wang, Woan-Shyuan; Huang, Yueh-Fang; Shyu, Yea-Ing L
Abstract: Background and Objectives: Improving quality of life for community-dwelling older persons with dementia symptoms (PWDS) and family caregivers requires promoting dementia-friendly communities (DFC). However, little is known regarding older Taiwanese Aboriginal PWDS' experiences of living in the community. We explored these experiences for older Atayal PWDS and their families in Taiwan. Research Design and Methods: This grounded theory research used in-depth interviews to explore the perspectives of older PWDS ( n = 4), their family members ( n = 3), and key persons ( n = 10) in an Atayal community in northern Taiwan. Data were analyzed using constant comparative analysis. Participants were interviewed between January and May 2015. Results: Participants' experiences were captured by the overarching concept of "low dementia awareness, high family-like ambience in the community." Despite the low/absent community awareness of dementia, older Atayal PWDS functioned as freely in the community as at home due to a family-like supportive environment. Aboriginal PWDS and their families also faced environmental challenges, e.g., environmental constraints and barriers to transportation access. Discussion and Implications: Our results suggest that this Aboriginal community and culture offer important DFC components, and these strengths could be further studied to enhance DFC models elsewhere. Despite these strengths in supporting PWDS, environmental challenges to transportation access still cause difficulties for PWDS and their families and need improvement. The Atayal community's low dementia awareness suggests that services introduced must be culturally appropriate and nondisruptive to existing supportive helping systems. Our study can be a model for future studies to understand and identify PWDS' needs in Indigenous communities.